Investigating the impact of wikis on writing performance of EFL students - Kızıl, Aysel Şahin (My University, 2015)
The use of technology has become an indispensable part of current generation of students often referred to as “digital natives” across the world. To make the educational activities compatible with the present day life itself, an increasing number of universities are seeking to provide students with more flexible and innovative language learning environments through Web 2.0 technologies. One powerful Web 2.0 tool that has recently attracted great attention in the field of second or foreign language teaching (L2) is wikis. Informed by the constructivist model of learning and by theories in L2 writing, this study aims to explore the impact of incorporating wikis into a writing course on writing performance of English as a foreign language (EFL) students. Through a quasi-experimental research design, students in the control group (n=17) received only in-class process-oriented writing instruction, and the experimental group students (n=20) integrated wiki tools into their writing process. The main data for the study were collected through writing performance pre-test and post-test. The findings indicated that using wikis had a positive impact on the overall writing performance of the participants in the experimental group. This study, therefore, recommends that EFL teachers employ wikis when they seek the ways of promoting their instructional practices through technology enhanced environment.
Kitap - Kitap İçinde Yayın (Bölüm ya da Makale)
Keywords: EFL learners; Social constructivist learning; Wiki